PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PT INDOMARCO PRISMATAMA AREA KABUPATEN SERANG - Risma Eka Desiyani; Lucky Dita Agustiansyah; Pipih Febriani (Gapenas Publisher, 2023)
Employee performance is one of the most important factors for the progress of the company. The development or failure of a company can be determined from how the performance of employees in the company, Good employee performance can make the company more advanced. Reward and Punishment is one of the supporting factors to improve employee performance for the better. Giving Rewards and Punishments for Employee Performance at PT Indomarco Prismatama Area Serang Regency in 2022 both partially and simultaneously. The research method used is quantitative, with a total research sample of 40 employees and processed with SPSS Version 2.2. The results of hypothesis testing (H1) the calculated value of the variable Reward tcalculate>ttable or 2.822> 2.026 with a significance level of 0.000 < 0.05 then Ha is accepted and Ho is rejected. (H2) the calculated value of the Punishment variable is 6.342 , this means that the value of tcalculated>ttable or 6.342> 2.026 with a significance level of 0.000 < 0.05 then Ha is accepted and Ho is rejected. (H3) Fcalculate value > Ftable, (137.877 > 3.25) with a significance level of 0.000 < 0.05, it can be concluded that Ha is accepted and Ho is rejected Based on the results of the study, it can be concluded that Reward affects employee performance, Punishment affects employee performance and simultaneously Reward and Punishment affect employee performance.